Factors Influencing Student Interest Participating in Campus Sports Activities - Ihsan, Andi; Muhammad Rizky Al Mufarid, Andi (ILIN Education Indonesia, 2025)
This study aimed to analyze the factors that influenced student interest in participating in campus sports activities at the Faculty of Sports Science and Health (FIKK), State University of Makassar (UNM). Student participation in campus sports activities was an important indicator in supporting character development, physical health, and academic achievement. The research method used was a quantitative approach with survey techniques using structured questionnaires distributed to 200 FIKK UNM students. Data analysis used descriptive statistical techniques and multiple regression to identify the dominant factors influencing student interest. The research results showed that there were five main factors that influenced student interest, namely intrinsic factors (personal motivation and health awareness), extrinsic factors (social support and sports facilities), academic factors (flexibility of lecture time), psychological factors (self-confidence and previous experience), and campus environment factors (accessibility and program availability). From the regression analysis results, intrinsic factors and sports facilities had the most significant influence on student interest with a coefficient of determination value of 67.3%. This study provided recommendations to the faculty to improve the quality of sports facilities, develop more varied sports programs, and create a campus environment that supported students' active lifestyles.